MAROQ: a resource allocation model driven through quality of experience. (2017) - D'Amato, André; Dantas, Mario; Macedo, Douglas D.J. De
The trend of grid computing available on the internet has generated challenges to the allocation of resources provided by this type of environment. Many of these challenges can be solved by the quality of experience paradigm that takes into account several context parameters. In this context, this paper presents the proposal of a new quality of experience-driven model for resource allocation for grids named MAROQ. We detail an experimental evaluation using context information with MAROQ that presents improvements of 7.46% on the average execution time of tasks.